(untitled) (Conferencea, 2022)
Modernization of the work of the planting unit, in addition to technological work, consists in improving and quality treatment of soils with low moisture and plant residues. The main directions of research on the modernization of the work of the planting unit and the development of technical means, as well as the main results of some studies conducted in these directions and their effectiveness are described.